Marketing Strategy Analysis of Insurance Companies in Indonesia - Amin Kuncoro; Livana PH; Suswadi (Jurnal Penelitian, 2026)
This study aims to examine the influence of marketing strategy dimensions on firm marketing performance in the Indonesian insurance sector. This study adopts a quantitative research design using a survey approach. Data were collected from marketing managers and senior staff of insurance companies operating in Indonesia. A total of 302 valid responses were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The research model examines the effects of market orientation, digital marketing capability, and relationship marketing on marketing performance. The results indicate that market orientation and digital marketing capability have a positive and significant effect on marketing performance. Relationship marketing also shows a significant influence, particularly in enhancing customer retention and trust. Digital marketing capability emerges as the most dominant factor affecting marketing performance in the Indonesian insurance industry. This study provides empirical evidence for insurance companies to prioritize customer-oriented strategies and digital marketing capabilities in improving marketing performance. These findings also offer insights for policymakers to support digital innovation and the development of insurance literacy in Indonesia, so that insurance companies can develop well.